Theoretical manual of 'YTU DEEP' SHIP motion program. (15th December 2022) - Olmez, Alper; Cakici, Ferdi
Abstract: The theoretical background for an in-house seakeeping code 'YTU DEEP' that calculates heave, roll and pitch motions of displacement ships is established in this paper. The code consists of two main parts: frequency and time-domain calculations. Two-dimensional added mass and damping coefficients are calculated by using Ursell's multipole expansion theory. Lewis conformal mapping technique is used together with Tasai's method to compute the sectional hydrodynamic coefficients. The strip theory of Salvesen et al. is used to obtain the global hydrodynamic coefficients. The damping values for the roll motion are calculated by using Ikeda's method. Excitation terms for pitch and heave motions are computed by using head seas approximation. The excitation term for roll motion is predicted by using low steepness waves approximation. For frequency domain code validation, Response Amplitude Operators for the AME CRC hulls motions are plotted at different forward speeds and in head waves. The results are compared with the experimental results and a good agreement is observed. For time-domain calculations, Cummins' method is utilized which used the sectional hydrodynamic coefficients in the frequency domain. The coupled pitch & heave and uncoupled roll motion equations are solved via the 4th order Runge Kutta Method. The solution of Cummins equations is tested for a container and passenger ship form simulation in bow quartering waves. A user-friendly interface is created for performing both frequency and time-domain simulations. Pre-processing, solution, and post-processing are applied with a MATLAB code. The proposed seakeeping code aims to create a quick and efficient ship motion program. Highlights: The theoretical background of frequency-time domain seakeeping code 'YTU DEEP' is explained. The RAO plots of heave, pitch and vertical acceleration of the ship are validated with existing experimental data. The time-domain code is given by Cummins' equation and a quick simulation is performed with the user-friendly interface.